JUSTIFICATION OF THE DIRECTIONS OF DEVELOPMENT OF THE ORGANIZATIONAL AND ECONOMIC MECHANISM OF BUSINESS MANAGEMENT OF MECHANICAL ENGINEERING - V. Kolosova; M. Kostin; M. Sazonova (Вестник университета)
The concept and the main directions of methodology of development of the organizational and economic mechanism of business management of mechanical engineering on the basis of reserve and factorial approach is proved. Teoretiko-methodological approaches to ensuring effective functioning and a sustainable development of the enterprise are specified.